1998
DOI: 10.1016/s0960-9822(98)70231-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of protein kinase B (AKT) in Drosophila

Abstract: The decision between survival and death is an important aspect of cellular regulation during development and malignancy. Central to this regulation is the process of apoptosis, which is conserved in multicellular organisms [1]. A variety of signalling cascades have been implicated in modulation of apoptosis, including the phosphatidylinositol (Pl) 3-kinase pathway. Activation of Pl 3-kinase is protective, and inhibition of this lipid kinase enhances cell death under several conditions including deregulated exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
120
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 21 publications
9
120
0
Order By: Relevance
“…Germ line clone (GLC) analysis removing both maternal and zygotic expression of Dakt1 resulted in embryos that exhibit ectopic and widespread apoptosis (Figure 1) (Staveley et al, 1998). We also demonstrated that the ectopic apoptosis in Dakt1 GLC embryos was independent of the grim, reaper and hid genes but could be suppressed through the expression of the baculoviral caspase inhibitor P35 (Staveley et al, 1998). This maternal role for Dakt1 prompted us to test for a potential role for PI3'K signaling in early Drosophila embryos.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Germ line clone (GLC) analysis removing both maternal and zygotic expression of Dakt1 resulted in embryos that exhibit ectopic and widespread apoptosis (Figure 1) (Staveley et al, 1998). We also demonstrated that the ectopic apoptosis in Dakt1 GLC embryos was independent of the grim, reaper and hid genes but could be suppressed through the expression of the baculoviral caspase inhibitor P35 (Staveley et al, 1998). This maternal role for Dakt1 prompted us to test for a potential role for PI3'K signaling in early Drosophila embryos.…”
Section: Resultsmentioning
confidence: 77%
“…Our previous study described a null mutant allele of Dakt1 that resulted in zygotic larval lethality (Staveley et al, 1998). Germ line clone (GLC) analysis removing both maternal and zygotic expression of Dakt1 resulted in embryos that exhibit ectopic and widespread apoptosis (Figure 1) (Staveley et al, 1998).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations